ChatGPT: five priorities for research - van Dis, Eva A. M.; Bollen, Johan; Zuidema, Willem; van Rooij, Robert; Bockting, Claudi L. (Nature (London), 2023)
Conversational AI is a game-changer for science. Since a chatbot called ChatGPT was released late last year, it has become apparent that this type of artificial intelligence (AI) technology will have huge implications on the way in which researchers work. ChatGPT is a large language model (LLM), a machine-learning system that autonomously learns from data and can produce sophisticated and seemingly intelligent writing after training on a massive data set of text. To prevent human automation bias - an over-reliance on automated systems - it will become even more crucial to emphasize the importance of accountability8. In the future, LLMs are likely to be incorporated into text processing and editing tools, search engines and programming tools. [...]they might contribute to scientific work without authors necessarily being aware of the nature or magnitude of the contributions.